2017
DOI: 10.1073/pnas.1615625114
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of cabbage phytoalexins from indole glucosinolate

Abstract: Brassica crop species are prolific producers of indole-sulfur phytoalexins that are thought to have an important role in plant disease resistance. These molecules are conspicuously absent in the model plant Arabidopsis thaliana, and little is known about the enzymatic steps that assemble the key precursor brassinin. Here, we report the minimum set of biosynthetic genes required to generate cruciferous phytoalexins starting from the well-studied glucosinolate pathway. In vitro biochemical characterization revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 46 publications
0
73
0
Order By: Relevance
“…These groups of compounds were described initially in 1940 and are considered phenolic-related compounds with highly diverse chemical structures and several bioactivities, including anti-cancer properties. They possess low molecular weight and are thought to serve as an important defense mechanism for the plant [54,55]. Brassicaceae members containing phytoalexins present an indolic ring with C3 substitutions with N and S atoms, which confers a unique structure among other vegetables.…”
Section: Phytoalexinsmentioning
confidence: 99%
See 1 more Smart Citation
“…These groups of compounds were described initially in 1940 and are considered phenolic-related compounds with highly diverse chemical structures and several bioactivities, including anti-cancer properties. They possess low molecular weight and are thought to serve as an important defense mechanism for the plant [54,55]. Brassicaceae members containing phytoalexins present an indolic ring with C3 substitutions with N and S atoms, which confers a unique structure among other vegetables.…”
Section: Phytoalexinsmentioning
confidence: 99%
“…The proposed biosynthetic pathway for phytoalexins formation includes brassinin formations from GSL; thereafter, other related phytoalexins are produced from brassinin. Klein and Sattely (2017) [55] reported that over 30 compounds arise from oxidative tailoring and rearrangement of Brassinin. Among edible cruciferous, phytoalexins have been reported in Brassica napus [56], Brassica oleracea [57], Brassica Juncea [58], Sinapsis alba [59], Wasabi japonica [60], and in Raphanus sativus [61].…”
Section: Phytoalexinsmentioning
confidence: 99%
“…The existence of such conjugates in planta is supported by the identification of indolyl-dithiocarbamate glucoside during engineering of brassinin (an IG-derived phytoalexin from Brassica spp.) biosynthesis in Nicotiana benthamiana (Klein and Sattely, 2017). GSTU13…”
Section: Discussionmentioning
confidence: 99%
“…GSLs and their hydrolysis products have also been shown previously to have antimicrobial properties (Tierens et al, 2001). Recently, more specific pathways of this antifungal mechanism were reported by Klein and Sattely (2017). These researchers identified some key enzymes required for the synthesis of the parent phytoalexin of Brassica plants called Brassinin from well-studied GSLs.…”
Section: Pseudocercosporella Capsellae (Ellis and Everh)mentioning
confidence: 99%